Hybrid fuel cell system degradation modeling methods: A comprehensive review - Vichard, L.; Steiner, N. Yousfi; Zerhouni, N.; Hissel, D. (Journal of power sources, 2021)
Last years, the fuel cell has become well-known as an efficient and clean energy converter being a potential alternative to internal combustion engines. However, despite being very promising, the durability of those systems is still a bottleneck. Most of the time, a fuel cell is integrated in a hybrid system which considers the fuel cell stack, the battery, and the balance of plant. To keep improving the durability of such a system, diagnostic and prognostic tools are of particular importance and to implement such tools, modeling the system is a mandatory step. The purpose of this paper is to propose a critical review of the existing methods to model all elements of a hybrid fuel cell system according to operating conditions and degradation. In this review, interactions and major degradation mechanisms occurring at all components will be presented and the physics-based models, data-driven and hybrid models of these components reviewed. Finally, methods will be discussed, and advantages and drawbacks will be summarized. •Complete hybrid fuel cell system modeling methods.•Hybrid fuel cell system degradation modeling.•Hybrid fuel cell system degradation mechanisms.•Hybrid fuel cell system balance of plant degradation.